Livedoid vasculopathy, calciphylaxis, and Martorell's hypertensive ulcer: update on ischemic ulcers due to impaired microcirculation of the lower limbs - Lacerda, Priscila Neri (2025)
Ischemic ulcers due to compromised microcirculation of the lower limbs cause painful ulcers that represent a challenge for the correct diagnosis and treatment. Livedoid vasculopathy, calciphylaxis, and Martorell's hypertensive ischemic ulcer are part of this group and present some similarities due to microvascular occlusive impairment. They are often misdiagnosed as inflammatory ulcers such as pyoderma gangrenosum and vasculitis. This review discusses the pathophysiology, risk factors, clinical aspects, differential diagnoses, histopathology, and presents a therapeutic update of livedoid vasculopathy, calciphylaxis, and Martorell's ulcer. Although they are less frequent causes of chronic ulcers, a correct diagnosis is essential to reduce the chance of erroneous therapies that may impact morbidity and mortality related to these conditions.